Topological and biological assessment of gene networks using miRNA- target gene data - Cingiz, Mustafa Ozgur; Diri, Banu (IEEE, 2019)
In recent years, different biological data sets obtained by the next generation sequencing techniques have enhanced the analysis of the underlying molecular interactions of diseases. In our study we apply ARNetMiT, C3NET, WGCNA and ARACNE algorithms on microRNA-target gene datasets to infer gene coexpression networks of breast, prostate, colon and pancreatic cancers. Gene coexpression networks are evaluated according to their topological and biological features. WGCNA based gene coexpression networks fits to scale free network topology more than other gene coexpression networks. In biological assessment there is no obvious difference found between gene coexpression networks which derived from different algorithms.
Keywords: miRNA- target genes; gene network inference algorithms; gene coexpression networks; scale free networks; gene ontology terms; Computer Science